Perancangan Standar Operasional Prosedur Laporan Penjualan Pada Perusahaan Manufaktur di Kota Batam - Muhammad Ikhlash; Nasrul Kahfi Lubis (Jurnal Penelitian Ekonomi Akuntansi, 2023)
The purpose of this study was to design a standard operating procedure for recording sales reports at a manufacturing company in Batam City. The method used in this research is descriptive method. Data collection was carried out using observation techniques, interviews, and documentation. The results of the study concluded that the company which was the object of research required a standard operating procedure as a guide for employees in carrying out work. The results of this study also produced a standard operating procedure for sales reports which were divided into two, namely daily sales reports and monthly sales reports